Small Particles, Big Impact: Nano Fertilizers Reshaping Indian Agribusiness - Lohar, Deepak; Singh, Dr. Matukdhari; Srivastava, Dr. R.P.; Baboo Tyagi, Dr. Dinesh (International Journal of Scientific Research and Management (IJSRM), 2023)
Maize, a globally significant staple crop, has long been synonymous with starch production. However, this review illuminates a lesser-explored facet of maize's biochemical profile, uncovering a treasure trove of hidden marvels beyond starch. We delve into the diverse world of maize varieties, each harboring a unique blend of bioactive compounds. From antioxidants, phytochemicals, and essential vitamins to minerals, maize offers an array of nutritional and therapeutic potential. Our exploration spans the health benefits conferred by these bioactive constituents, demonstrating their role in disease prevention and overall well-being. Moreover, the pharmaceutical and industrial sectors stand to gain from maize's biochemical versatility, with applications ranging from drug development to sustainable materials. This review underscores the pressing need for continued research into maize's biochemical wonders.In essence, this article celebrates maize's multifaceted nature, transcending its starch-centric reputation. We invite readers to recognize and harness the potential of maize's lesser-known biochemical marvels, fostering innovation in agriculture, nutrition, and beyond.